2021
DOI: 10.3390/catal11050527
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated NOLA™ Fit 5500 Lactase—An Economically Beneficial Way to Obtain Lactose-Free Milk at Low Temperature

Abstract: The current requirements of industrial biocatalysis are related to economically beneficial and environmentally friendly processes. Such a strategy engages low-temperature reactions. The presented approach is essential, especially in food processes, where temperature affects the quality and nutritional value foodstuffs. The subject of the study is the hydrolysis of lactose with the commercial lactase NOLA™ Fit 5500 (NOLA). The complete decomposition of lactose into two monosaccharides gives a sweeter product, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Furthermore, their activity at 12 °C and source of isolation—microorganisms Generally Recognized As Safe—correspond to the industrial requirements of food processes and ensure the preservation of the nutritional value of the processed raw materials [ 14 ]. These observations were confirmed by literature studies on dairy processes and low-temperature biocatalysis [ 9 , 27 , 31 – 33 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Furthermore, their activity at 12 °C and source of isolation—microorganisms Generally Recognized As Safe—correspond to the industrial requirements of food processes and ensure the preservation of the nutritional value of the processed raw materials [ 14 ]. These observations were confirmed by literature studies on dairy processes and low-temperature biocatalysis [ 9 , 27 , 31 – 33 ].…”
Section: Discussionsupporting
confidence: 80%
“…Although CAT does not directly participate in glucose decomposition, its presence was necessary to maintain the high enzymatic activity of GOX, through the decomposition of H 2 O 2 , which acts as inhibitor toward GOX [ 9 ]. The proposed strategy referred to previous results, in which authors discussed the importance of product inhibition during NOLA-induced lactose hydrolysis [ 27 ] and indicated the critical process parameters (pH of medium and oxygen concentration) that accompany the enzymatic decomposition of glucose by a two-enzyme cascade with GOX and CAT [ 9 ].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It was challenging to achieve at least an 80% hydrolysis yield using β-galactosidase, due to the formation of galactose and glucose in the presence of permeate salts, acids and proteins. Czyzewska et al [29] confirmed that the presence of glucose in the hydrolysed substrate strongly affects the activity of NOLA™ Fit5500 β-galactosidase. Inhibition slows the rate of hydrolysis and decreases the enzymatic activity, which, in turn, prolongs the hydrolysis reaction [30].…”
Section: Enzymatic Hydrolysis and Transgalactosylation In Whey Permeatementioning
confidence: 93%